Morphological features and prognostic significance of tip variant of focal segmental glomerulosclerosis: Study of an Indian cohort - Malhotra Kiran; Prasad Narayan; Jain Manoj (Wolters Kluwer Medknow Publications, 2010)
Context: Several attempts have been made to formulate a morphologic classification of focal segmental glomerulosclerosis (FSGS) variants with therapeutic and prognostic implications. Differences in study populations such as racial profile or therapy offered have hampered attempts to define prognostic variables in FSGS. Literature reveals conflicting results regarding the prognostic significance of tip variant of FSGS in different populations. Aims: To study the clinical and pathologic parameters in tip and not otherwise specified (NOS) variants of FSGS, in subjects from the Indian subcontinent with prognostic significance. Materials and Methods: First we performed a retrospective analysis of patients with biopsy proven primary FSGS, diagnosed between January 2004 and December 2008. Twenty cases of tip variant were encountered in adult population and similar numbers of adult cases of NOS variant were randomly selected. Renal biopsies were studied using light and immunofluorescence microscopy. Medical records for clinical data at presentation, biopsy and three monthly follow-up intervals were reviewed and compared between two groups. Results: At presentation, clinical profiles for the two groups were similar; however, significant differences in histological parameters and clinical outcome in tip and NOS variant cases were noted. Interstitial fibrosis and tubular atrophy were significantly higher in NOS variant. Greater response rate to steroid therapy was observed in tip variant cases while higher proportion of NOS variant cases showed renal failure. Conclusion: Analysis of histological parameters is important in assessing the outcome of tip and NOS variants. Tip variant signifies a better prognostic subset for a population of Indian origin affected by FSGS.